Cerebral amyloid angiopathy-related inflammation (CAARI): case report - Karol Adam Makarewicz; Karolina Zaryczańska; Karolina Machowska-Sempruch; Anna Bajer-Czajkowska; Piotr Gołofit; Ewa Gabrysz-Trybek; Przemysław Nowacki (Folia Neuropathologica, 2019)
Cerebral amyloid angiopathy-related inflammation is a new disease entity whose proper diagnosis may be difficult due to the fact that the early phase and radiological image resemble other conditions such as intracerebral haemorrhage or proliferative disorder. Also, the brain biopsy, which is an important part of the evaluation to confirm the diagnosis and rule out mimics, cannot be performed in each patient. In this paper we present the case of a 58yearold man who was correctly diagnosed with cerebral amyloid angiopathy-related inflammation (CAARI) based on the results of the histopathological examination of the brain tissue, which was possible mainly owing to the inclusion of the expansive process as the underlying cause in the initial differentiation. Further progression of the disease, despite applying treatment of increasing intensity in response to progressive deterioration of the patient’s condition, revealed the multiplicity of clinical courses that a new and not easily pinpointed entity can take.